Integration of study material in the problem-based learning method - S. Becker; M. J. Viljoen; Y. Botma; I. J. Bester (AOSIS, 2003)
Throughout the world educators are starting to realise that integrated curricula reflect the "real world". Students learn how to integrate theory appropriately with practice and it stimulates higher order thinking skills. Problem-based learning (PBL) was used as a learning strategy in an integrated undergraduate programme. A quantatative non-experimental design, a survey, was used to determine how problem-based learning influences integration of learning by the students. Using a purposive sampling method all the first-year nursing students (43) at the University of the Free State participating in the programme were included in the study. Data was collected by means of a student perception questionnaire (SPQ).